2022
DOI: 10.1108/medar-04-2022-1640
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability, non-financial, integrated, and value reporting (extended external reporting): a conceptual framework and an agenda for future research

Abstract: Purpose This paper aims to develop a conceptual framework for extended external reporting (EER) influences (EERI), including sustainability, non-financial, integrated and value reporting. Using the Environmental Legitimacy, Accountability, and Proactivity (ELAP) framework as the base, we modify its proposed concepts and linkages using relevant conceptual models, prior reviews and findings of recent studies on EER. This paper presents contributions of the special issue on “non-financial and integrated reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 87 publications
0
18
0
1
Order By: Relevance
“…As previously discussed, accounting research on the GRI shows how the GRI contributed to promoting multi-stakeholder accountability, helping organisations identify material issues, spread common material issues among organisations and measuring their sustainability performance through indicators. In addition, prior studies have identified several related research opportunities (Hsiao et al , 2022; De Villiers et al , 2022a, 2022b; Molinari and De Villiers, 2021). These research areas are likely to continue to inspire future research; however, given recent developments, different research questions and perspectives are likely to come to the fore.…”
Section: Avenues For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously discussed, accounting research on the GRI shows how the GRI contributed to promoting multi-stakeholder accountability, helping organisations identify material issues, spread common material issues among organisations and measuring their sustainability performance through indicators. In addition, prior studies have identified several related research opportunities (Hsiao et al , 2022; De Villiers et al , 2022a, 2022b; Molinari and De Villiers, 2021). These research areas are likely to continue to inspire future research; however, given recent developments, different research questions and perspectives are likely to come to the fore.…”
Section: Avenues For Future Researchmentioning
confidence: 99%
“…In turn, the current changes in sustainability standard-setting, and the entry of the IFRS/ISSB, are likely to provide novel research opportunities and practical implications. Therefore, this paper draws upon the recent call for global standards for sustainability reporting and the ongoing changes in sustainability reporting standard-setting, including the regulatory initiatives and the de facto reporting standards aimed at harmonising sustainability reporting (La Torre et al , 2020b; De Villiers et al , 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of CSR research is impressive, and numerous CSR reviews have been performed. For example, De Villiers, Hsiao, et al (2022), Hsiao et al (2022), Andrew and Baker (2020), De villiers & Hsiao, 2018, De Villiers et al (2014, 2017), Dumay et al (2016), and Gray et al (1995) conduct literature reviews on CSR disclosure; there are literature reviews on the economic consequences of CSR (e.g., firm value and firm risk) (Albuquerque et al, 2019; Khlif et al, 2015; Orlitzky, 2001, 2008; Orlitzky et al, 2003; Orlitzky & Benjamin, 2001; Rost & Ehrmann, 2017), the theories used in the CSR literature (De Villiers & Van Staden, 2010; Deegan, 2002; Spence et al, 2010), CSR performance (Wood, 1991a, 1991b, 2010; Wood & Jones, 1995), and CSR assurance services (Cohen & Simnett, 2014; Farooq & De Villiers, 2017). Differing from the previous literature reviews, we are interested in reviewing CSR research with an emphasis on CSR databases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This would be beneficial for both the preparers and the users of these reports. Specifically, the GRI or the World Business Council for Sustainable Development could develop specific requirements or principles on the use of visual elements to enhance the completeness and impartiality of information in the sustainability/CSR reports, and thereby improve the quality and transparency of the reports (Boiral, 2013; Busco et al , 2013; Lombardi and Secundo, 2020; De Villiers et al , 2022a). The principle of impartiality or balanced reported information, should be extended wherever possible to include visual elements, particularly photographs.…”
Section: Discussionmentioning
confidence: 99%
“…It may be permissible to make the content of the reports more visually appealing by using, for example, idealistic photographic imagery of smiling employees and innocent-looking children; however, if such visual disclosure deviates from the actual business practices of the company, then there must be regulations and guidelines to check or audit them. Currently, there are no GRI guidelines regarding how companies should use visual elements in their reporting of social and environmental issues (Boiral, 2013; De Villiers et al , 2022a; De Villiers et al , 2022b). Clearly, to improve the reports’ realism, more robust guidelines on the use of multiple visual elements in sustainability/CSR reports are required.…”
Section: Discussionmentioning
confidence: 99%